Komunikasi Ekspresif Gaya Berpakaian Adat Remaja Hindu di Media Sosial - Ni Nyoman Shinta Paramesti Lestari; I Ketut Putu Suardana; Rieka Yulita Widaswara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study discusses how Hindu teenagers express their cultural and religious identity through traditional clothing that they display on social media, especially Tik Tok. In today's digital era, social media has become an important place for young people to design and convey their self-image, including through visual presentations such as traditional clothing. The method used in this study is a descriptive qualitative approach with content analysis of four posts from one account of a Hindu teenage girl who shows herself wearing Balinese traditional clothing. The purpose of this study is to understand the form of expressive communication that emerges from the visualization of traditional clothing styles and the symbolic meanings contained therein. This study shows that the traditional clothing styles displayed not only function as cultural preservation, but also as a medium for conveying religious values, ethnic identity, and pride in Balinese Hindu cultural heritage. Tiktok social media in this case allows the spread of these cultural messages to a wider audience by building a positive narrative about the identity of Hindu teenagers amidst the influence of cultural globalization. This study contributes to the understanding of how teenagers use social media as a tool for expressive cultural communication, as well as the importance of maintaining the continuity of traditions through digital media that are relevant to the lives of the younger generation.